G33k
  • G33k
Factor the expression.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
i can help u
dr0zier99
  • dr0zier99
no
zepdrix
  • zepdrix
yay

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
ANSWER: (3x - 2)(x - 4) CHECK: (3x - 2)(x - 4) = 3x(x) + 3x(-4) - 2(x) - 2(-4) = 3x² - 12x - 2x + 8 = 3x² - 14x + 8
anonymous
  • anonymous
Write 2 sets of parentheses. (_____)(_____) = Look at the first term's factors. 3x² = 3x * x Write 3x and x at the beginning of each set of parentheses. (3x_____)(x_____) = Look at the last term's factors. You want the pair that will add up to the -14x when multiplied by the 3x and x you already have. 1 * 8 ===> (3x * 1) + (1x * 8) = 3x + 8x = 11x <== wrong pair 2 * 4 ===> (3x * 2) + (1x * 4) = 6x + 4x = 10x <== wrong pair 4 * 2 ===> (3x * 4) + (1x * 2) = 12x + 2x = 14x <== wrong pair 8 * 1 ===> (3x * 8) + (1x * 1) = 24x + 1x = 25x <== wrong pair -1 * -8 ===> (3x * -1) + (1x * -8) = -3x + -8x = -11x <== wrong pair -2 * -4 ===> (3x * -2) + (1x * -4) = -6x + -4x = -10x <== wrong pair -4 * -2 ===> (3x * -4) + (1x * -2) = -12x + -2x = -14x <== right pair -8 * -1 ===> (3x * -8) + (1x * -1) = -24x + -1x = -25x <== wrong pair -4 * -2 is the right pair. Since -4 is paired with 3x and 3x is on the outside, write -4 on the outside. (3x_____)(x - 4) = Since -2 is paired with x and x is on the inside, write -2 on the inside. (3x - 2)(x - 4)
anonymous
  • anonymous
no problem
anonymous
  • anonymous
need any more help
Zarkon
  • Zarkon
(3x - 2)(x - 4) is not the answer to the question asked
dr0zier99
  • dr0zier99
no
anonymous
  • anonymous
what is the matter i did it right
zepdrix
  • zepdrix
The middle term is 14x, not -14x.
anonymous
  • anonymous
ohh my bad
anonymous
  • anonymous
@G33k i am sorry for giving u the wrong answer to this equation
G33k
  • G33k
It's fine
anonymous
  • anonymous
kk

Looking for something else?

Not the answer you are looking for? Search for more explanations.